Construction of Evaluation Model of Tennis Skills and Tactic Level and Application of Grey Relational Algorithm - Ling Wang (Journal of Sensors, 2022)
Based on the application characteristics of the world’s elite tennis players’ skills and tactics, this paper establishes the evaluation model of skill and tactic level. According to the principle of normal distribution, taking the overall average as the reference value and the overall standard deviation as the discrete distance, the deviation method commonly used in sports statistics is adopted to formulate the grade evaluation standard. The standard is divided into five evaluation grades: excellent, good, passing, poor, and extremely poor. The equivalent evaluation scale of diagnostic indexes of tennis skill and tactic level is established. It also discusses many factors that characterize the skills and tactics of tennis singles. At the same time, it introduces the grey relational algorithm, constructs the evaluation model of skills and tactic level, and makes an example application. Through experimental analysis, it is concluded that this model can be applied not only to the diagnosis of individual athletes but also to the evaluation of a sports team. This article is aimed at further enriching the analysis system of tennis skills and tactics.